Promotion of self-care for people with leprosy: educational intervention in the light of Orem's theory - Jeane Lima Cavalcante; Karine Nascimento da Silva; Rayanne de Sousa Barbosa; Maria Corina Amaral Viana; Dayanne Rakelly de Oliveira; Edilma Gomes Rocha Cavalcante
ABSTRACT Objective: To report the experience of promoting self-care for people with leprosy during educational interventions in the light of Orem's theory. Method: Experience report of an educational intervention. The analysis was carried out in the light of Orem's theory of nursing systems, in the support-education system. Results: The guidelines for self-care took into account actions to prevent nasal dryness; and promote decreased sensitivity, joint swelling, pain and dryness in the hands and feet. Final considerations: The educational intervention to promote self-care favored the protagonism of the person with leprosy who started to carry out preventive care with continuity and autonomy.